KUALITAS PELAYANAN PASIEN PESERTA JAMINAN KESEHATAN MASYARAKAT DI PUSKESMAS ENTIKONG KABUPATEN SANGGAU - Ria Resti Fauzi E.01109021 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this study is The Quality of Jamkesmas Members’ Health Service at Entikong Public Healt Centre Kabupaten Sanggau West Kalimantan. The purpose of this study is to give the understanding about public health service through the program of JAMKESMAS as there are still many citizens complaining about the quality of the service given by Entikong Public Health Centre in order to enhance the quality of further health service to be more effective. This study uses the analytical descriptive method with the qualitative technique in the data processing. In this study, the public health service covers four aspects including the easiness in dealing the problem, getting the appropriate service, getting the equal treatment, getting the transparent and honest treatment. Result of the analysis shows that there is lack of clear instructions, the honesty, the security, and the equality of giving the treatment by the officers to the patients of JAMKESMAS.Keywords : Service Quality, JAMKESMAS program, Easiness and Transparency.